Civil-military relations in Chile under the Constitution of 1823: An explanation of its rules and political context - Verbal Stockmeyer, Valentina (Derecho Público Iberoamericano, 2015)
This article addresses the issue of civil-military part of the Constitution of 1823. It points to relationships determining how that civilian elites sought to subordinate the military, especially considering the system of checks and balances of government in military field. And, secondly, to study the image that had ruling elites over the military. Thus, it seeks to fill a gap in historiography about the role of the military in the period of formation of the Republic.